A long, hard look at Gray v Thames Trains Ltd - Goudkamp, J (Hart Publishing, 2015)
This chapter addresses the landmark decision in Gray v Thames Trains Ltd. Although it was decided in the twilight years of the House of Lords, it was the first occasion on which the House had considered at any length the doctrine of illegality in the tort setting. The precise scope of the rules laid down in Gray is somewhat uncertain, but it is clear that they are the starting point for thinking about how the doctrine applies in negligence cases. Considering the growing significance of the doctrine in this area, Gray is, therefore, an important case. The goal of this chapter is to explore it generally, focusing on Lord Hoffman?s speech, which is the principal opinion. It takes account of how Gray has been understood by subsequent decisions. It will be argued that the Gray, owing to Lord Hoffmann?s speech, brought about a significant improvement in the law (for which there was much scope). However, it will also be contended that the reasons given by Lord Hoffmann for embracing the rules that he laid down are suspect in certain respects, and that there are grounds for thinking that those rules can be improved. Finally, it will be contended that Gray has been marginalised somewhat by two subsequent decisions at the highest level, namely, Stone & Rolls Ltd v Moore Stephens and Hounga v Allen, and that its status is therefore open to some doubt.